UNDERLYING INTERESTS OF ENACTMENT REGIONAL AUTONOMY - Wismar Harianto (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The process of implementing regional autonomy involves various institutions such as the Regional Government, the Central Government, the House of Representatives of the Republic of Indonesia, the Regional Representative Council of the Republic of Indonesia, and the Regional Autonomy Advisory Council. If in the process of implementing regional autonomy, it is known that the Region or several Regions are unable to organize Regional Autonomy, then a Regional Merger is carried out based on the agreement of the region concerned or the results of an evaluation from the Central Government.